Practical application of an extended container transport problem for the transport of bulk cargo - Krčmář, Pavel; Kalčevová, Jana; Lagová, Milada, 1941-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2010)
The thesis concerning practical application of a container transport problem in a case of a company trading kitchen appliances, concretely optimizing costs of the transport of goods from three warehouses to five stores with four different types of cars.
Vedoucí práce: Jana Kalčevová
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2010
Rok obhajoby 2010
Keywords: statistika a ekonometrie [obor bakal. práce]; bakalářské práce; bachelor's theses